Combining Geometric Semantic GP with Gradient-Descent Optimization - Pietropolli, Gloria (2022)
Pietropolli, G., Manzoni, L., Paoletti, A., & Castelli, M. (2022). Combining Geometric Semantic GP with Gradient-Descent Optimization. In E. Medvet, G. Pappa, & B. Xue (Eds.), Genetic Programming. EuroGP 2022: 25th European Conference, EuroGP 2022 Held as Part of EvoStar 2022 Madrid, Spain, April 20–22, 2022 Proceedings (pp. 19-33). (Lecture Notes in Computer Science; Vol. 13223). Springer. https://doi.org/10.1007/978-3-031-02056-8_2